The Politics of Nursing: The Neoliberal Transformation of Nursing Emergency Care - Lauzier, Kim (Université d'Ottawa / University of Ottawa, 2023)
This study aims to understand the organization of Emergency Department (ED) nurses in Ontario after years of restructuring and cuts made to the healthcare system. The news is currently filled with ED closures across the country due to a shortage of nurses and high hospital occupancy. The recruitment and retention of nurses in the ED has proven extremely difficult due in part to the Ontario government's Bill 124 capping nurses' wage increases at 1%. This wage freeze is inscribed in a larger rationale present internationally advocating for efficiency and marketization of all spheres of life, healthcare included. Most of the literature published on the work of ED nurses refers to ideas of performance of flow. Using Institutional Ethnography (IE) as an approach and governmentality, more specifically neoliberalism, as a perspective, this study maps the ruling relations influencing the work of nurses in the ED. It also uncovers how the neoliberal discourse was not only internalized but applied by nurses in their work environment. The methodological approach and perspective used in this study highlight how a new rationale was implemented in the management and funding of healthcare, which then led to transforming the rationale of providing care in the ED. The ED now delivers care following a supply chain rationale employing technologies of governmentality such as Electronic Medical Records (EMR) to entice a specific conduct from nurses in order to meet the demands of the market. This new rationale, coupled with the implementation and sustaining of the technologies of governmentality, has come to completely transform what an ED nurse is nowadays. This new ED subject is responsible for most aspects of care, flow, and even her own training and security. The findings suggest that the use of algorithms based on best practices (such as medical directives) came to further erode the decisional power of nurses, resulting in "checkbox" practice.
Keywords: Emergency Nursing Care; Neoliberalism; Institutional Ethnography; Governmentality